Much ado about murder - Duncan, Elizabeth J. (Duncan, Elizabeth J. Shakespeare in the Catskills mysteries., 2017)
When the up-and-coming new British director for the Catskills Shakespeare Theater Company's production of "Much Ado About Nothing" is found dead, a presumed suicide, costume designer Charlotte Fairfax investigates.